China-Taiwan mask diplomacy : wooing Southeast Asia? - Kliem, Frederick (2020)
While the US has largely abdicated its global leadership amidst the COVID-19 crisis, the People’s Republic of China and Taiwan are leveraging on the pandemic as a soft power opportunity. Southeast Asia receives particular attention.